Facts and challenges for the autoimmunologist. Lessons from the second Colombian autoimmune symposium (2012)
The first Colombian Autoimmune Symposium took place in Medellin in February 2005 [1]. Since then, much progress has been made. Among others, two facts have marked the recent history of the field of autoimmunity. The first one consists of the demonstration of a common origin for autoimmune diseases (ADs) [2–11] and, the second one, corresponds to the introduction of the autoimmunologist as the specialist devoted to diagnosis and therapy of ADs [12–15]. The fact that ADs share several clinical signs and symptoms, physiopathological mechanisms and genetic factors has been called autoimmune tautology and indicates that they have a common origin [9]. This concept had its origins in the clinical observations describing a possible shift of one disease to another or the fact that more than one AD may coexist in a single patient (i.e. polyautoimmunity) or in the same family (i.e. familial autoimmunity or autoimmune aggregation). The term “kaleidoscope of autoimmunity” [16–19] was coined as a result of the observations while the term “mosaic of autoimmunity” was introduced to explain the multifactorial origin and diversity of ADs expression [20,21]. In fact, different combinations of the many factors involved in autoimmunity as complex diseases produce varying and unique clinical pictures that represent the wide spectrum of ADs [20,21].